Occurrence of QACE/QACEΔ1 genes and their correlation with class 1 integrons in Salmonella enterica isolates from poultry and swine - Rungtip Chuanchuen (2018)
In this study, a total of 122 Salmonella enterica isolates from poultry and swine were assessed for susceptibility to clinically important antibiotics and to benzalkonium chloride (BKC). All isolates were examined for the presence of the antiseptic resistance genes qacE and qacEΔ1 and intl1 (class 1 integrase). The intl1-positive strains were further investigated for the presence of the 3′ conserved region. The results demonstrated widespread distribution of qacEΔ1 (27%) but no isolate with qacE was observed. The intl1 gene was identified in 23 isolates (70%) with qacEΔ1. All of the intl1-postive strains carried qacEΔ1 in 3′ conserved segment, confirming that the qacEΔ1 gene is linked to the integrons. Increased MIC value to BKC was independent of the presence of qacEΔ1, and multiple antibiotic-resistant bacteria were no more tolerant to BKC than the non-multidrug resistant strains, regardless of the presence of qacEΔl.